2016
DOI: 10.1097/id.0000000000000334
|View full text |Cite
|
Sign up to set email alerts
|

Vertical Bone Augmentation Using Bone Marrow–Derived Stem Cells

Abstract: BMSCs delivered with a collagen/β-TCP linked scaffold can provide improved new bone formation that is comparable with autogenous bone block graft through vertical guided bone regeneration technique.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 31 publications
0
10
0
Order By: Relevance
“…Recently, several studies have explored the effects of mesenchymal stem cells, which have the capability to differentiate into bone, cartilage, and muscle, on bone regeneration [67]. The use of stem cells with a synthetic or xenogenic bone graft enhanced bone regeneration when compared with a bone graft alone, possibly due to the osteogenic and osteoinductive properties of stem cells [89]. Previous studies have shown that a combination of stem cells with bone graft material improved bone regeneration [1011].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, several studies have explored the effects of mesenchymal stem cells, which have the capability to differentiate into bone, cartilage, and muscle, on bone regeneration [67]. The use of stem cells with a synthetic or xenogenic bone graft enhanced bone regeneration when compared with a bone graft alone, possibly due to the osteogenic and osteoinductive properties of stem cells [89]. Previous studies have shown that a combination of stem cells with bone graft material improved bone regeneration [1011].…”
Section: Introductionmentioning
confidence: 99%
“…The surface area of the rabbit calvaria is larger compared with that of the rat and up to four experimental groups may be compared in the same animal (58,59). Compared with the rat model, the rabbit model is also advantageous because it is possible to take an equal amount of autologous bone as a control group (47). The rabbit calvaria onlay model for block bone material is easier to apply compared with the VGBR model; block bone material is placed on the calvarial bone and fixed with screws.…”
Section: Different Experimental Models Of Vertical Bone Augmentationmentioning
confidence: 99%
“…In contrast, other studies [28, 7477] have shown that, owing to the strong hydrophobicity of this material, it does not promote cell adhesion. Surface treatments or association with biomolecules, such as collagen, alginate, or polypeptides, are therefore necessary to facilitate the interaction between the cells and the biomaterial [75]. In fact, Wang et al demonstrated that the incorporation of MSCs in nanoparticles mixed with calcium phosphate cements (CPC), inserted into cranial defects in nude rats, promoted bone regeneration [28].…”
Section: Scaffolds With Stem Cellsmentioning
confidence: 99%
“…In fact, Wang et al demonstrated that the incorporation of MSCs in nanoparticles mixed with calcium phosphate cements (CPC), inserted into cranial defects in nude rats, promoted bone regeneration [28]. Thus, these scaffolds are suitable for bone regeneration, showing good results in newly formed bone volumes in animal studies [75, 78]. …”
Section: Scaffolds With Stem Cellsmentioning
confidence: 99%